SHRM-CP/SHRM-SCP certification practice exams - Kelly, William D.; Simon-Walters, Joanne (McGraw-Hill Education, 2019)
More than 500 accurate practice questions and answers for the SHRM-CP and SHRM-SCP exams This all-new book arms you with hundreds of practice questions for the two new Society for Human Resource Management exams--the SHRM Certified Professional (SHRM-CP) and the SHRM Senior Certified Professional (SHRM-SCP) exams. All questions simulate those on the actual tests in content, style, tone, format, and difficulty, and are accompanied by in-depth answer explanations for the correct AND incorrect answer choices. SHRM-CP/SHRM-SCP Certification Practice Exams is logically organized by exam domains, allowing you to focus on specific topics and tailor your study to areas of strength and weakness. Two pre-assessment tests--one for each exam--are also included to gauge your exam readiness and determine a course for self-study." Written by a pair of seasoned HR professionals " Supplements SHRM-CP/SHRM-SCP Certification All-in-One Exam Guide " Covers all SHRM-CP and SHRM-SCP functional areas Electronic content includes: " All of the questions from the book in a customizable exam engine--practice answering questions by exam topic or take complete, timed exams " PDF copy of the book